Preliminary investigation on the effectiveness of Allium sativum on selected fungal dermatophytes. - Suano, Chris Enelue Sancho
This study conducted on February 1998 is a preliminary investigation to determine the effectiveness of Allium sativum (garlic) on selected fungal dermatophytes. Alcoholic and aqueous extracts from whole garlic cloves were done by making a 1:2 weight to volume ratio. Four concentrations (25, 50, 75, 100) were separately made from both the previously prepared alcolohic and aqueous mixtures in order to test the antifungal activity of each at the different levels used against the five dermatophyte species, specifically, Epidermophyton floccosum, Microsporum canis, Microsporum gypseum, Trichophyton rubrum and Trichophyton tonsurans. The alcoholic extract completely inhibited the growth of all the test organisms at the various levels of concentration used. The aqueous extract, however, arrested totally the growth of only three species-E. floccosum, M. canis and M. gypseum-while slowing down the mycelial growth of T. rubrum and T. tonsurans. It was found out that T. rubrum was the most resistant among the five species while E. floccosum, M. canis and M. gypseum were all very sensitive to the garlic clove extract.